Resilience Analysis of Jatiluhur and Sutami Dam Storage Capacity Against Climate Change in Java - Ahmad Hidayawan (CV. Get Press Indonesia, 2026)
The structural integrity of Indonesia's aging dam infrastructure faces unprecedented stress due to accelerating climatic volatility. This research investigates the widening gap between original hydraulic design parameters and contemporary extreme weather patterns observed during the 2020–2025 period. Utilizing a quantitative longitudinal design, this study evaluates six strategic dams including Jatiluhur, Sutami, and Gajah Mungkur by integrating secondary datasets from BMKG, BPS, and the Ministry of PUPR. The analysis focuses on the impact of a 22.4% increase in extreme rainfall frequency and a 14.2% reduction in upstream forest cover on reservoir resilience. Results indicate a critical 17.21% mean escalation in peak inflow magnitudes (), effectively eroding the national dam Resilience Index to a precarious average of 0.83. Furthermore, sedimentation rates have surged to 1.45 times design projections, causing a 0.75-meter reduction in freeboard safety margins. These findings suggest that legacy